2016
DOI: 10.3126/jnps.v36i2.14828
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of G6PD Deficiency in a Tertiary Care Hospital in South India

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the commonest red cell enzymopathy affecting red cell metabolism. Its presentation can vary from drug induced haemolysis to neonatal jaundice with a prevalence ranging from 0-27% in India. The objective of this study was to find out the incidence of G6PD deficiency in babies delivered in our hospital and to assess its contribution in causing neonatal jaundice. 500 babies were screened for G6PD deficiency by Fluorescent spot test method. All the babies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…6 Recent reports like a study from South India also, revealed no case of G6PD deficiency when they studied 500 neonates screened for G6PD by Fluorescent spot test method. 12 It is thought that as the gene of G6PD Mediterranean allele passed through the North and then spread throughout the adjoining areas by several contacts between the Mediterranean people and Indians, it is not unusual that the distribution of G6PD deficient allele among Indian population, would be comparatively higher in the North and West zone. 6 Regarding the eastern zone, the deficiency of G6PD has been least studied in this part of the country.…”
Section: Discussionmentioning
confidence: 99%
“…6 Recent reports like a study from South India also, revealed no case of G6PD deficiency when they studied 500 neonates screened for G6PD by Fluorescent spot test method. 12 It is thought that as the gene of G6PD Mediterranean allele passed through the North and then spread throughout the adjoining areas by several contacts between the Mediterranean people and Indians, it is not unusual that the distribution of G6PD deficient allele among Indian population, would be comparatively higher in the North and West zone. 6 Regarding the eastern zone, the deficiency of G6PD has been least studied in this part of the country.…”
Section: Discussionmentioning
confidence: 99%